Dominant currency pricing in international trade of services - Jo\~ao Amador; Joana Garcia; Arnaud Mehl; Martin Schmitz (European Central Bank (ECB), 2024)
We analyze, for the first time, how firms choose the currency in which they price transactions in international trade of services and investigate, using direct evidence, whether the US dollar (USD) plays a dominant role in services trade. Drawing on a new granular dataset on extra-European Union exports of Portuguese firms broken down by currency, we show that currency choices in services trade are active firm-level decisions. Firms that are larger and rely more on inputs priced in foreign currencies are less likely to use the domestic currency to export services. Importantly, we show that the USD has a dominant role as a vehicle currency in trade of services - but to a lesser extent than in trade of goods - and that this is not just due to differences in the geography of trade. An external validity test based on macro data available for Portugal and six other European countries confirms this finding. In line with predictions from recent theoretical models, our results are consistent with the lower prevalence of USD in services trade arising from a lower openness of services markets and a stronger reliance of services on domestic inputs.
Keywords: F14; F31; F41; 330; dominant currency paradigm; international trade; services